2021
DOI: 10.1038/s41598-021-98165-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to mortality in septic patients in Vietnamese intensive care units from a subgroup analysis of MOSAICS II study

Abstract: Sepsis is the most common cause of in-hospital deaths, especially from low-income and lower-middle-income countries (LMICs). This study aimed to investigate the mortality rate and associated factors from sepsis in intensive care units (ICUs) in an LMIC. We did a multicenter cross-sectional study of septic patients presenting to 15 adult ICUs throughout Vietnam on the 4 days representing the different seasons of 2019. Of 252 patients, 40.1% died in hospital and 33.3% died in ICU. ICUs with accredited training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 44 publications
0
26
0
4
Order By: Relevance
“… 3 , 5 , 6 Furthermore, severe febrile illness outcomes likely differ owing to patterns of comorbidities and the availability of intensive care. 11 It is unsurprising that studies of existing illness severity scores derived in high-income countries have shown mixed results for predictive performance for adverse outcomes in LMICs. 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“… 3 , 5 , 6 Furthermore, severe febrile illness outcomes likely differ owing to patterns of comorbidities and the availability of intensive care. 11 It is unsurprising that studies of existing illness severity scores derived in high-income countries have shown mixed results for predictive performance for adverse outcomes in LMICs. 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…(4, 36) In our study, however, the hospital and ICU mortality rates are higher than that reported in the international Extended Study on Prevalence of Infection in Intensive Care (EPIC III) study (30.3% [2404/7936] and 23.6% [1870/7936], respectively). (37) These differences might be because the EPIC III included ICU-acquired infection and not specifically sepsis,(37) and also might be because the patients, pathogens, and clinical capacity to manage sepsis differ considerably between HIC and LMIC settings(7, 33, 37).…”
Section: Discussionmentioning
confidence: 99%
“…This multicentre observational, cross-sectional, point prevalence study is part of the Management of Severe sepsis in Asia’s Intensive Care unitS II (MOSAICS II) study,(32, 33) which collects data on the management of sepsis in Asia. In this study, we used only data from Vietnam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional treatment for sepsis involves antibiotics, plasma, oxygen and other blood products to help with thromboembolic complications, and vasoactive medications and intravenous fluids for stabilizing the blood circulation and maintaining blood pressure [9]. There have been various sepsis studies in the Southeast Asia including Bangladesh [10,11], India [11][12][13], Indonesia [14,15], Nepal [6,11,16,17], Pakistan [7], Sri Lanka [18,19], Thailand [14,20] and Vietnam [14,21]. Appropriate management of sepsis is required, especially in Southeast Asian countries where the mortality rate is high [9].…”
Section: Introductionmentioning
confidence: 99%